2020
DOI: 10.1002/cctc.202000508
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Cycloaddition of Epoxides and Carbon Dioxide Catalyzed by Triazole‐Bridged Bisphenol

Abstract: 1,2,3‐triazole‐bridged bisphenol has been developed as organocatalyst in the coupling of CO2 and epoxides. In the absence of halide co‐catalyst, halomethyl‐substituted epoxides reacted with 1 bar CO2, while a series of aryl‐substituted epoxides were transformed into cyclic carbonates in 57–95 % yields at 120 °C and 10 bar pressure. 1,2,3‐triazole‐bridged bisphenol is thus among the most efficient organocatalysts that are active in the absence of both metal and halide. For alkyl‐substituted epoxides, good yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 134 publications
0
22
0
Order By: Relevance
“…The power of tandem C(sp 2 )−H sulfonylation and a pyrazole annulation without employing any transition metal catalyst or reagent is demonstrated by the Wan and Sheng groups for the synthesis of 4‐sulfonyl pyrazoles [18] . Another metal‐free cycloaddition of CO 2 and epoxides in the presence of 1,2,3‐triazole‐bridged bisphenol catalyst is presented by the teams of Yuan and Yao [19] . The synthesis of renewable RGO@CuI nanocomposites and their subsequent application as nanocatalysts to construct diverse N‐heterocycles (benzimidazole and spiropyrroline derivatives) via aerobic and anaerobic single electron transfer (SET) reactions is presented by Rawat and co‐workers [20] .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The power of tandem C(sp 2 )−H sulfonylation and a pyrazole annulation without employing any transition metal catalyst or reagent is demonstrated by the Wan and Sheng groups for the synthesis of 4‐sulfonyl pyrazoles [18] . Another metal‐free cycloaddition of CO 2 and epoxides in the presence of 1,2,3‐triazole‐bridged bisphenol catalyst is presented by the teams of Yuan and Yao [19] . The synthesis of renewable RGO@CuI nanocomposites and their subsequent application as nanocatalysts to construct diverse N‐heterocycles (benzimidazole and spiropyrroline derivatives) via aerobic and anaerobic single electron transfer (SET) reactions is presented by Rawat and co‐workers [20] .…”
Section: Figurementioning
confidence: 99%
“…[18] Another metal-free cycloaddition of CO 2 and epoxides in the presence of 1,2,3-triazolebridged bisphenol catalyst is presented by the teams of Yuan and Yao. [19] The synthesis of renewable RGO@CuI nanocomposites and their subsequent application as nanocatalysts to construct diverse N-heterocycles (benzimidazole and spiropyrroline derivatives) via aerobic and anaerobic single electron transfer (SET) reactions is presented by Rawat and coworkers. [20] The groups of Lu and Cai report a Co-based heterogeneous catalyst, supported on N,P co-doped porous carbon (Co@NCP), for the synthesis of quinoxalines from onitroanilines and biomass-derived diols.…”
mentioning
confidence: 99%
“…56 More recently, some single-component halogen-and metalfree homogeneous catalysts were reported to operate under slightly milder conditions (T: 100-120 °C, PCO2: 10-20 bar) based on Schiff bases, 57,58 tertiary amines, [59][60][61] ammonium salts 62 and N-heterocyclic compounds (triazoles, azolates, 2aminopyridines, DBU, adducts of imidazolium compounds). [63][64][65][66][67][68] Similarly, metal-and halogen-free heterogeneous catalyst were recently reported that operate efficiently in the 120-140 °C temperature range and at CO2 pressures ≥ 10 bar. 61,[69][70][71] Therefore, the cycloaddition of CO2 to epoxides by halide-free homogeneous and heterogeneous organocatalysts under atmospheric pressure remains underreported; Verpoort et al have very recently reported that nitrogen-rich triazole rings bearing carboxylic acid functionalities were competent halogen-free organocatalysts for atmospheric CO2 cycloaddition to several epoxides in the 75-100 °C temperature range.…”
Section: Introductionmentioning
confidence: 98%
“…A large number of catalysts have been developed to catalyse the cycloaddition reaction, including transition metals (e.g., Cr, [15][16][17] Fe, [18][19][20][21] Co, [22][23][24][25][26][27] and Zn [28][29][30][31][32][33] ), main group metals (e.g., Mg, [34][35][36] Al, [37][38][39][40][41][42] Ca [43][44][45][46] ), rare-earth metal catalysts [47][48][49][50][51][52][53][54][55][56][57] and organocatalysts. 5,[58][59][60][61][62][63]…”
Section: Introductionmentioning
confidence: 99%